Klèbun Babine’: Praktik, Gaya Kepemimpinan dan Faktor Pendorong Keberhasilan Memimpin Pemerintah Desa - Hoiril Sabariman; Siti Kholifah; Yayuk Yuliati; Wawan Sobari (Kafa`ah: Journal of Gender Studies, 2019)
The village women leader (Klèbun Babine’) in Madura is not fully considered. They were merely a symbol and administrative officer. While the policy determinant is on the husband or family of the male party. In contrast, the case study of women Head Village chief Ponteh successfully run the village government without the influence of the husband or family from the male side. The leadership of Klèbun Babine' is not inferior to the village head led by men. The case study revealed the leadership practices, leadership styles and driving factors of Klèbun Babine ' in the village government. By doing observasion, in-depth interviews and playing documentation revealed that Klèbun Babine's leadership performed by paddling the community as a child, giving freedom to the official village to work well and to tighten on Primary community interests from personal interests. Klèbun Babine' implements the style of masculine-transformational leadership with the hallmark of totality in leading based on Divine value (transcendentalism). The driving factor of Klèbun Babine' success in the first village government are the individual ability, communication to bring out a layer of community, second, community suppor and active, third, the maximum role of village government. This study shows a new fact about Klèbun Babine ' that is not a symbol and administrative officer but it can lead the village government in rural Madura.